Colonialism and Education - Nwanosike, Oba .F; Onyije, Liverpool Eboh (Richtmann Publishing, 2011)
Colonialism and education has been identified as instruments used by European powers to dominate and subjugatethird world countries and Africa in particular. Colonialism is the policy or practice of acquiring full or partial political control overanother country, occupying it with settlers, and exploiting it economically. It was a response to the economic needs of industrialcapitalist Europe who desire colonies in order to have access to raw materials of the colonies, to have markets for sale ofmanufactured goods of the home country and field for the investment of surplus capital. Colonialism ravaged Africa like wild firewith disastrous consequences and the instrument used for that purpose is education. This same education was later used as aweapon to fight colonialism. This paper is therefore to explore why and how colonialism was imposed on African nations andhow education was used as a two-edged sword for the propagation and abolition of colonialism. â€œTo know the present we mustlook into the past and to know the future, we must look into the past and present.â€